Risk Factors for Central Lymph Node Metastasis in CN0 Papillary Thyroid Carcinoma: A Systematic Review and Meta-Analysis. - Wei Sun; Xiabin Lan; Hao Zhang; Wenwu Dong; Zhihong Wang; Liang He; Ting Zhang; Siming Liu (PLoS ONE)
Background Central lymph node metastasis (CLNM) is common in papillary thyroid carcinoma (PTC). Prophylactic central lymph node dissection (PCLND) for patients with clinically negative central compartment lymph nodes (CN0) remains controversial. The phrase "clinically negative" is used to indicate that patients exhibited no clinical evidence of CLNM by ultrasonography (US) or computerized tomography (CT) preoperatively. In this study, we analyze the risk factors for CLNM in CN0 patients. Methods The PUBMED and SCIE databases were systematically searched for works published through January 31, 2015. All of the patients included in this study underwent thyroidectomy+PCLND. Revman 5.3 software was used to analyze the data. Results Twenty studies and 9084 patients were included in this meta-analysis. The following variables were associated with an increased risk of CLNM in CN0 patients: age < 45 years (OR = 1.59, 95% CI = 1.42-1.78, p<0.00001), male sex (OR = 1.95, 95% CI = 1.63-2.32, p<0.00001), multifocality (OR = 1.43, 95% CI = 1.22-1.67, p<0.00001), tumor size > 2 cm for PTC patients (OR = 2.98, 95% CI 2.08-4.28, p<0.00001) or tumor size > 0.5 cm for papillary thyroid microcarcinoma (PTMC) patients (OR = 2.30, 95% CI = 1.71-3.09, p<0.00001), location of the primary tumor in the central area and low pole (OR = 1.86, 95% CI = 1.48-2.33, p<0.00001), lymphovascular invasion (OR = 4.35, 95% CI = 2.24-8.46, p<0.0001), extrathyroidal extension (OR = 2.27, 95% CI = 1.76-2.94, p<0.00001), and capsular invasion (OR = 1.72, 95% CI = 1.39-2.41, p<0.00001). PTC (tumor size > 1 cm) exhibited a higher risk factor associated with CLNM than PTMC (tumor size < 1 cm) (OR = 2.83, 95% CI = 2.15-3.72, p<0.00001). Bilateral tumors (OR = 1.21, 95% CI = 0.92-1.58, p = 0.17) and lymphocytic thyroiditis (OR = 0.88, 95% CI = 0.71-1.09, p = 0.25) had no association with CLNM in CN0 patients. Conclusions Our systematic review identified several clinical features associated with CLNM in CN0 patients, including age, sex, multifocality, size, location, lymphovascular invasion, capsular invasion, and extrathyroidal extension. These factors should guide the application of PCLND in CN0 patients.